Dark days : fugitive essays - Reeves, Roger (Graywolf Press, 2023)
"The first book of nonfiction from an award-winning poet combines memoir, theory and criticism to find common purpose between Black and Indigenous peoples and reflects on the new meanings of silence, protest, fugitivity, freedom and ecstasy"--